The Future of preferential trade arrangements for developing countries and the current round of WTO negotiations on agriculture - angermann, Stefan (FAO RomeIT, 2002)
Attempts to provide some tentative responses to questions such as should developing countries strongly defend their trade preferences, and try to improve them; what are the benefits and costs of the preferences; how do trade preferences compare to other forms of assistance for economic development; do developing countries stand to lose a lot as agricultural trade is further liberalised and preference margins are eroded?